Bone mineral density in flatwater sprint kayakers - Flodgren, G.; Hedelin, R.; Henriksson-Larsen, K. (Calcified Tissue International, 1999)
To elucidate the possible skeletal benefits of the muscular contractions and the nonweight-bearing loading pattern associated with kayaking, we investigated the bone mineral density (BMD, g/cm2) of 10 elite kayakers, six males and four females, with a median age of 19 years. Each subject was compared with the mean value of two matched controls. BMD of the total body, head, ribs, humerus, legs, proximal femur (neck, wards, trochanter), spine, lumbar spine, and bone mineral content (BMC, g), of the arms was obtained using a dual energy X-ray absorptiometer (DXA). Body composition was also assessed. The kayakers had a significantly (P < 0.05-0.01) greater BMD in most upper body sites: left and right humerus (10.4% and 11. 7%), respectively, ribs (6.4%), spine (10.9%), and a greater BMC of the left and right arm (15.7% and 10.6%, respectively). No significant differences in the BMD of the total body, head, or any of the lower body sites were found, except for the pelvis, which was significantly greater in kayakers (5.1%). The controls had a significantly lesser lean body mass (10.4%) and greater percentage of body fat (19.5%) than the kayakers. Bivariate correlation analysis in the controls demonstrated significant and strong relationships between BMD in upper body sites and lean body mass, weight, and fat; the effects of training seem to outweigh most such relationships in kayakers. In conclusion, it seems that the loading pattern and muscular contractions associated with kayaking may result in site-specific adaptations of the skeleton.